The decision to install flue gas desulphurisation on Medupi Power Station: identification of environmental criteria contributing to the decision making process - Singleton, Tyrone C. (My University, 2010)
Survival of society has always been dependent on ensuring that a balance is continually maintained between the variables of social needs, resources and the environment. The difficulty is that these three elements are more often than not in conflict with each other. Arguably without such conflicts environmental decision making would be far simpler in the knowledge that the potential solution, although not pleasing everyone would be capable of responding to a range of ecological and economic concerns. Environmental decision making requires a structured holistic approach that allows for the evaluation of alternative solutions against an array of often conflicting objectives, although no specific decision making structure is advocated multi criteria objective decision making provides a means to achieve such ends. The methodology provides for the identification of all objectives which are then used to evaluate alternative scenarios or solutions against. The following research report seeks to identify the environmental criteria that would need to be considered as part of a multi-criteria decision making structure. The report highlights the complexities and often conflicting elements that exist even within the narrow scope of environmental objectives. All discussions are made with specific reference to Eskom’s requirement to comply to future air quality legislation and the potential requirement to install flue gas desulphurisation technologies on its Medupi Power Station. Legislative, technological, water and air quality issues are identified and explored as to how they should be evaluated as part of the overall environmental decision making criteria. Through the identification of the environmental criteria it is hinted that Eskoms narrow mandate of electricity production at the lowest cost could potentially prevent the organisation of fully engaging in a holistic decision making process.